2020
DOI: 10.4103/jomt.jomt_45_19
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of adverse events following immunization, its prevalence and actions of mothers of children aged 0–23 months in a tertiary health institution in Jos, North Central Nigeria

Abstract: Background: Adverse Event Following Immunization (AEFI) is any unfavorable event occurring following vaccination related to the vaccine administration and or its handling. AEFI can lead to death or a life-threatening condition requiring hospitalization with or without permanent sequel. Hence, this study was conducted to determine the knowledge of AEFI among mothers of children aged 0–23 months, its prevalence and actions of mothers of following AEFIs. Methodology: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
3
5
1
Order By: Relevance
“…The prevalence of AEFI reported in this study is at par with figures reported from a previous study in north-central Nigeria 13 and southern Nigeria. 14 Astonishingly, our figures were higher than results from an earlier study in our setting, 7 and from findings in a similar study from India.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The prevalence of AEFI reported in this study is at par with figures reported from a previous study in north-central Nigeria 13 and southern Nigeria. 14 Astonishingly, our figures were higher than results from an earlier study in our setting, 7 and from findings in a similar study from India.…”
Section: Discussionsupporting
confidence: 71%
“…12 In Nigeria, a prevalence of 34.9% to 46.5% was reported across different parts of the country. 7,13,14 This study assessed the prevalence and patterns of adverse events following immunisation among children in Kano, Nigeria. Findings from this study could be helpful for health care providers, immunisation programme managers, and development partners supporting the programme in preparing strategies for improved management of the immunisation programme in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…This rate was consistently lower than the rates reported in North Central [ 12 ], North West [ 13 ], and South South [ 14 ] Nigeria, although it was slightly higher than the rate reported in an earlier study in North West Nigeria in 2016 [ 15 ]. The consistently different rates across regions, including the rate reported in this study, may be a result of contextual differences in study settings, differences in the education levels of mothers between regions as documented in past studies [ 12 15 ], coincidental events that may have been reported as AEFIs by mothers in some of the studies due to a close temporal association with the timing of immunization, different vaccine handling and storage techniques, differences in the manufacturers of vaccines across zones, and, notably, ethnic and genetic differences between children, given that many studies from different zones of the country employed a similar cross-sectional research design. There may also be differences among mothers in their level of awareness about reporting AEFIs across zones, which is also closely linked to the education level of mothers.…”
Section: Discussioncontrasting
confidence: 56%
“…This was a healthcare facility-based descriptive cross-sectional study conducted with mothers of children aged 0 to 24 months who attended any of the 3 leading immunization clinics in Ile-Ife, Osun, Nigeria. The minimum sample size was estimated using the formula for single proportion [ 11 ] and was calculated to be 422 based on an AEFI prevalence of 46.5% [ 12 ], an error margin of 5%, and a 95% confidence interval (CI) given a possible 10% non-response rate. The study enrolled mothers with at least 1 eligible child aged 0 to 24 months who had previously completed a full vaccination regimen and mothers who brought their children to 1 of the 3 immunization clinics for the child’s ninth month of vaccinations and who consented to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…10 Major determinants about AEFI (knowledge and response required) were directly proportional to employment and educational status of the mother. 9 In our survey, lesser participants were aware about AEFI (28.6%) compared to above data owing to inclusion of all age respondents. A study by Bansal and Mahajan 2017 observed that, parents knowing AEFIs had positive attitude towards vaccination because they knew symptoms are transient and manageable.…”
Section: Discussionmentioning
confidence: 70%